2013
DOI: 10.1152/ajplung.00424.2012
|View full text |Cite
|
Sign up to set email alerts
|

Wt1-expressing progenitors contribute to multiple tissues in the developing lung

Abstract: Cano E, Carmona R, Muñoz-Chápuli R. Wt1-expressing progenitors contribute to multiple tissues in the developing lung. Am J Physiol Lung Cell Mol Physiol 305: L322-L332, 2013. First published June 28, 2013 doi:10.1152 doi:10. /ajplung.00424.2012velop from paired endodermal outgrowths surrounded by a mesodermal mesenchyme. Part of this mesenchyme arises from epithelialmesenchymal transition of the mesothelium that lines the pulmonary buds. Previous studies have shown that this mesothelium-derived mesenchyme con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
70
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 44 publications
5
70
1
Order By: Relevance
“…We used the highest tamoxifen dose that was compatible with survival of embryos to term, and labeled the large majority (81 6 1.7%) of mesothelial cells. PMC-derived mesenchymal cells (PMCDCs) were found within the lung mesenchyme ( Figure 1B), consistent with having undergone an EMT, as reported previously (9)(10)(11). The entry of fetal PMCs into lung mesenchyme was confirmed using cultured fetal lung explants, where mesothelium was selectively labeled using the cell-tracking dye, 5-chloromethylfluorescein diacetate (CMFDA) ( Figure E2).…”
Section: Fate Of Pmc-derived Cells In the Developing Lungsupporting
confidence: 83%
See 2 more Smart Citations
“…We used the highest tamoxifen dose that was compatible with survival of embryos to term, and labeled the large majority (81 6 1.7%) of mesothelial cells. PMC-derived mesenchymal cells (PMCDCs) were found within the lung mesenchyme ( Figure 1B), consistent with having undergone an EMT, as reported previously (9)(10)(11). The entry of fetal PMCs into lung mesenchyme was confirmed using cultured fetal lung explants, where mesothelium was selectively labeled using the cell-tracking dye, 5-chloromethylfluorescein diacetate (CMFDA) ( Figure E2).…”
Section: Fate Of Pmc-derived Cells In the Developing Lungsupporting
confidence: 83%
“…These cells, like other mesothelial cells, express the transcription factor, Wilms' tumor 1 (Wt1), and Wt1-driven expression of constitutive Cre or inducible CreERT2 alleles has been used to trace the fate of PMCs during lung development, postnatal lung homeostasis, and lung disease, with conflicting results (3,(9)(10)(11). During lung development, one study using a constitutive Wt1-Cre transgene reported that PMCs contribute to vascular SMCs (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both Tbx4 À and Wt1-based experimental systems traced the progeny of mesothelial cells to smooth muscle and endothelial populations, as well as fibroblasts identified by desmin and/or the absence of other lineage markers. 34,35,42 These results also indicate that mesothelium is not the main source of pericytes or fibroblasts in the adult lung, but may instead contribute to rare fibroblast subgroups whose distinguishing features and ancestry remain ambiguous. Together, these largely concordant findings demonstrate both the close relationships between pericytes and resident fibroblasts and the heterogeneity among these populations ( Figure 2 and Table 2).…”
Section: Mesothelial Cellsmentioning
confidence: 86%
“…Wt1 expression is restricted to the intermediate and lateral plate mesoderm during development, structures that give rise to the omentum, mesentery and the mesothelium lining the organs of the visceral cavity. Consequently, these studies showed that the mesothelium provides a source of adipocyte progenitors for VAT but not SAT (Asahina et al, 2011;Cano et al, 2013;Chau et al, 2014;Rinkevich et al, 2012). These studies also showed that Wt1 positive progenitors are not the sole source of adipocytes because, depending on the individual VAT depot, only 30-80% of adipocytes in adult mice derive from cells that express Wt1 during embryonic development (Chau et al, 2014) (Fig.…”
Section: Subcutaneous and Visceral Adipocytes Have Different Developmmentioning
confidence: 95%